2020
DOI: 10.1186/s12979-020-00197-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of monocyte NF-κB p65/RelA signaling in a cohort of older medical patients, age-matched controls, and healthy young adults

Abstract: Background: Altered monocyte NF-κB signaling is a possible cause of inflammaging and driver of aging, however, evidence from human aging studies is sparse. We assessed monocyte NF-κB signaling across different aging trajectories by comparing healthy older adults to older adults with a recent emergency department (ED) admission and to young adults. Methods: We used data from: 52 older (≥65 years) Patients collected upon ED admission and at follow-up 30-days after discharge; 52 age-and sex-matched Older Controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
(101 reference statements)
1
14
0
Order By: Relevance
“…Given that high suPAR is associated with a lower effectiveness of the immune system, as illustrated by the elevated risk of disease progression and adverse events, as well as its associations with inflammation and multiple indicators of accelerated aging and functional decline, suPAR may be a useful biomarker of SCI that can be used to quantify the level of inflammaging and immunosenescence. In support of this, we recently reported elevated suPAR levels in a patient population characterized by accelerated aging and multiple signs of immunosenescence, including reduced capacity to respond to immune stimulation, defects in NF-κB signaling, and higher levels of inflammatory biomarkers (CRP, IL-6, IL-18, TNFα, growth differentiation factor 15 [GDF15]) and NLRP3 inflammasome expression compared to age-matched and young healthy controls ( 183 ).…”
Section: Discussionmentioning
confidence: 74%
“…Given that high suPAR is associated with a lower effectiveness of the immune system, as illustrated by the elevated risk of disease progression and adverse events, as well as its associations with inflammation and multiple indicators of accelerated aging and functional decline, suPAR may be a useful biomarker of SCI that can be used to quantify the level of inflammaging and immunosenescence. In support of this, we recently reported elevated suPAR levels in a patient population characterized by accelerated aging and multiple signs of immunosenescence, including reduced capacity to respond to immune stimulation, defects in NF-κB signaling, and higher levels of inflammatory biomarkers (CRP, IL-6, IL-18, TNFα, growth differentiation factor 15 [GDF15]) and NLRP3 inflammasome expression compared to age-matched and young healthy controls ( 183 ).…”
Section: Discussionmentioning
confidence: 74%
“…Activation of the NF-kB pathway in macrophages leads to the production of proinflammatory cytokines IL-6 and TNF-alpha. An analysis of monocytes from hospitalized individuals (elderly vs. young) showed higher NF-kB activation but reduced responses to TLR stimulation in elderly populations versus younger controls [81]. Importantly, these studies found that with age, continued stimulation of the NK-kB pathway may lead to immune tolerance and reduced response to subsequent stimuli.…”
Section: Monocyte and Macrophage Traffic To Tissues With Hiv Siv And ...mentioning
confidence: 80%
“…With age, there are increased plasma concentrations of inflammatory mediators (IL-6, IL-10, sICAM-1, sVCAM-1, and MCP-1) that promote monocyte extravasation and subsequent tissue inflammation [79]. Additionally, studies have focused on monocyte and macrophage cytokine dysregulation and NF-kB pathway activation (discussed below) as drivers of inflammation [34,80,81] in the context of HIV and SIV; and HIV, SIV, and aging.…”
Section: Monocyte and Macrophage Traffic To Tissues With Hiv Siv And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Minor injuries or traumas are handled in a separate Emergency Room. Other results of the study regarding medication, inflammation and biological aging have been published elsewhere [ 19 , 20 , 21 ]. Reporting of the study follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for cohort studies [ 22 ].…”
Section: Methodsmentioning
confidence: 99%